2020
DOI: 10.1088/1757-899x/735/1/012067
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Damping Effects of Various Vibration Reduction Measures

Abstract: Field measurements are the most effective and direct way to evaluate the effects of vibration reduction measures. Through field measurements, this study examined the actual damping effects and vibration transfer characteristics of five vibration reduction measures for subway systems, namely, steel spring floating slabs, resilient short crossties, double-layer nonlinear damping fasteners, Vanguard fasteners and rubber floating slabs. The vibration level and 1/3 octave frequency division vibration level was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…It was shown that the rubber pads could effectively reduce the vertical natural frequency of the deck plate, except for the fundamental frequency, but they had little effect on the horizontal natural frequency. Rubber-pad floating slabs are used extensively on subway lines [21][22][23][24], which proves that rubber can effectively reduce the vibration of floating slabs. The lower the stiffness of the rubber pad under the slab, the lower the natural frequency of the floating slab.…”
Section: Introductionmentioning
confidence: 98%
“…It was shown that the rubber pads could effectively reduce the vertical natural frequency of the deck plate, except for the fundamental frequency, but they had little effect on the horizontal natural frequency. Rubber-pad floating slabs are used extensively on subway lines [21][22][23][24], which proves that rubber can effectively reduce the vibration of floating slabs. The lower the stiffness of the rubber pad under the slab, the lower the natural frequency of the floating slab.…”
Section: Introductionmentioning
confidence: 98%